2011
DOI: 10.3897/zookeys.90.1121
|View full text |Cite
|
Sign up to set email alerts
|

New earthworm species of the genus Amynthas Kinberg, 1867 from Thailand (Clitellata: Megascolecidae)

Abstract: Four new species of terrestrial earthworms from the zebrus-group in the genus Amynthas Kinberg, 1867, are described from Nan province, north Thailand: Amynthas phatubensis sp. n., from Tham Pha Tub Arboretum, Amynthas tontong sp. n., from Tontong Waterfall, Amynthas borealis sp. n., from Chaloemprakiat district, and Amynthas srinan sp. n., from Srinan National Park.After comparing with the two closely related Laos species Amynthas chandyi Hong, 2008 and Amynthas namphouinensis Hong, 2008, the four new species … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Several surveys of terrestrial earthworms in Thailand have been published (Gates 1939(Gates , 1972Somniyam & Suwanwaree 2009;Bantaowong et al 2011aBantaowong et al , 2011bBlakemore 2011;Bantaowong et al 2014), but many localities in Thailand and nearby areas and various types of microhabitats are still unexplored. Recently, Bantaowong et al (2014) summarized the knowledge about the Thailand earthworm fauna and reported 45 species.…”
Section: Introductionmentioning
confidence: 99%
“…Several surveys of terrestrial earthworms in Thailand have been published (Gates 1939(Gates , 1972Somniyam & Suwanwaree 2009;Bantaowong et al 2011aBantaowong et al , 2011bBlakemore 2011;Bantaowong et al 2014), but many localities in Thailand and nearby areas and various types of microhabitats are still unexplored. Recently, Bantaowong et al (2014) summarized the knowledge about the Thailand earthworm fauna and reported 45 species.…”
Section: Introductionmentioning
confidence: 99%
“…The following abbreviation used in the figures of the anatomy are as appeared in Bantaowong et al (2011a , b ): sp , spermathecal pores; fp , female pore; gm , genital markings; mp , male pores; sc , spermathecae; sv , seminal vesicles; pg , prostate gland; ic , intestinal caeca.…”
Section: Materials and Methodsmentioning
confidence: 99%
“…The following abbreviations used in the descriptions of anatomy are as appeared in Bantaowong et al (2011a, b), Chanabun et al (2011, 2012a, b): wi , wings; gm , genital markings; he , hearts; sv , seminal vesicles; sc , spermathecae; ov , ovaries; np , nephridia. …”
Section: Methodsmentioning
confidence: 99%